2007
DOI: 10.1002/chem.200700838
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of (−)‐Indicol by a Carbene Cyclization–Cycloaddition Cascade Strategy

Abstract: The first total synthesis of a secodolastane, (-)-indicol, has been accomplished. The key reaction is a rhodium(II)-mediated carbene cyclization-cycloaddition cascade, by which the core bicyclo[5.4.0]undecane skeleton was assembled. In this one-pot reaction, a domino series of transformations resulting in the construction of three sigma bonds and three stereocenters was realized in good yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Conversion of 7 to 9 proceeded uneventfully by sodium chlorite oxidation 9 to give 8 followed by standard generation of the diazoketone function. 10 Gratifyingly, subjecting TES ether 9 to acetic acid in THF/water 11 led to the sensitive alcohol 10 in high yield, whereas deblocking of the tbutyldimethylsilyl (TBS) analog of 9 prepared from 5 in a corresponding fashion could not be achieved without substantial destruction of the non-stabilized diazoketone unit. Unfortunately, however, all attempts to convert 10 to the corresponding vinylsulfonate met with failure, and only the known chloride 12 12 was isolated from treatment of 10 with vinylsulfonyl chloride (11).…”
Section: Resultsmentioning
confidence: 99%
“…Conversion of 7 to 9 proceeded uneventfully by sodium chlorite oxidation 9 to give 8 followed by standard generation of the diazoketone function. 10 Gratifyingly, subjecting TES ether 9 to acetic acid in THF/water 11 led to the sensitive alcohol 10 in high yield, whereas deblocking of the tbutyldimethylsilyl (TBS) analog of 9 prepared from 5 in a corresponding fashion could not be achieved without substantial destruction of the non-stabilized diazoketone unit. Unfortunately, however, all attempts to convert 10 to the corresponding vinylsulfonate met with failure, and only the known chloride 12 12 was isolated from treatment of 10 with vinylsulfonyl chloride (11).…”
Section: Resultsmentioning
confidence: 99%
“…[10] Other research groups have appliedt his reaction to the synthesis of complex natural products, including aspidophytine, [11] gallicadiol and isogallicadiol, [12] polygalolides Aa nd B, [13] and platensimicin. [14] We have applied this reaction to the total syntheses of (À)-pseudolaric acid A, [15a] (À)-indicol, [8] and synthetic studies towards isocurcumenol. [15b] The synthesis of 2 began with the ring opening of oxirane (S)-6 by the cuprate derived from 3-methylbut-3-enylmagnesium bromide, and this afforded alcohol 7 with the first stereogenic centre (Scheme 2).…”
Section: Synthesis Of Ketonementioning
confidence: 99%
“…In 2007, we accomplished the total synthesis of (À)-indicol. [8] Ours ynthesis featured the construction of the [5.4.0]carbobicyclic core using ar hodium-catalyzed carbene cyclization cycloaddition cascade in one step. This success encouraged us to extendo ur studies toward the synthesis of the tricyclic dolastanes.…”
Section: Introductionmentioning
confidence: 99%
“…In the same area, Chiu et al have reported total syntheses of natural and biologically active pseudolaric acid A, 69 and (-)-indicol, on the basis of rhodium-catalysed intramolecular domino carbonyl ylide formation-1,3dipolar cycloaddition reactions of chiral a-diazoketones derived from commercially available glycidol derivatives, which allowed the core bicyclo [5.4.0]undecane skeleton to be assembled. 70 As shown in Scheme 1.45, treatment of a chiral a-diazoketone with a catalytic amount of chiral catalyst [Rh 2 {(S)-bptv} 4 ] in benzotrifluoride at -40 1C afforded the corresponding domino product in 82% yield as a 1.6 : 1 mixture of two diastereoisomers. The major diastereomer was separated and then converted into pseudolaric acid A through 10 steps.…”
Section: Carbene Sequencesmentioning
confidence: 99%